2015
DOI: 10.1055/s-0035-1567830
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Studies and Hepatitis C: Harvesting the Benefits of the Genomic Revolution

Abstract: Utilizing genome-wide association studies (GWASs) to examine the variation in hepatitis C virus (HCV) phenotypes has led to quantum improvements in our understanding of both the genetic basis and the underlying pathogenesis of HCV infection. In this context, the discovery of interferon lambda polymorphisms is unique with far reaching implications that extend well beyond HCV to various other liver and extrahepatic diseases. In this review, we summarize the data on the impact of GWASs on our understanding of HCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 150 publications
(179 reference statements)
0
13
1
Order By: Relevance
“…Pretreatment intrahepatic ISG expression is a strong predictor of the response to IFN-a-based therapy in HCV but not HBV. (3) We found no correlation between rs7574865 and the expression of four ISGs (IFI27, ISG15, RSAD2, and HTATIP2) in 85 liver biopsy samples previously shown to be a strong predictor of response in CHC. (4) Thus, whereas ethnic differences cannot be excluded, differences in the hepatic immune response to HBV and HVC are more likely responsible for the lack of association between rs7574865 and the outcomes of HCV infection.…”
Section: Polymorphisms In Stat4 Are Not Associated With Treatment Rescontrasting
confidence: 68%
See 1 more Smart Citation
“…Pretreatment intrahepatic ISG expression is a strong predictor of the response to IFN-a-based therapy in HCV but not HBV. (3) We found no correlation between rs7574865 and the expression of four ISGs (IFI27, ISG15, RSAD2, and HTATIP2) in 85 liver biopsy samples previously shown to be a strong predictor of response in CHC. (4) Thus, whereas ethnic differences cannot be excluded, differences in the hepatic immune response to HBV and HVC are more likely responsible for the lack of association between rs7574865 and the outcomes of HCV infection.…”
Section: Polymorphisms In Stat4 Are Not Associated With Treatment Rescontrasting
confidence: 68%
“…Our recent data from the LEAN trial indicated that 48 weeks of treatment with the once-daily glucagon-like peptide-1 analogue, liraglutide, resulted in NASH resolution (with no worsening of fibrosis) in 39% (9 of 23) of patients with NASH compared to 9% (2 of 22) who received placebo control. (3) We applied the Vilar-Gomez et al NASH resolution score (1) to our LEAN trial cohort, which included patients with advanced fibrosis and morbid obesity, to assess its accuracy in identifying the absence or presence of NASH resolution after pharmacological intervention. Using the lower threshold of <46.15, the score had a specificity of 94% (95% confidence interval [CI], 81-98), because it correctly identified 32 of 34 patients without NASH resolution.…”
Section: To the Editormentioning
confidence: 99%
“…These studies should however be interpreted with caution given the potential risk for selection bias as more subjects with responder genotypes would have cleared HCV on IFN-based therapy. The net effect would be enrichment of the group of HCC with those carrying the non-response IFNk genotype [92].…”
Section: Genetic Variation In Interferon Lambda and Other Liver Diseamentioning
confidence: 99%
“…A number of examples of genetic variations have been reported for drugs treating a variety of diseases such as hepatitis C infection 30, cancers 31, 32, blood coagulation et al 33, representing a new frontier in drug therapy and personalized medicine 34, 35. For example, subtypes of CYP450s differ among races and individuals, resulting in variations in drug degradation rate 36, 37 and thus constituting an important factor in personalized drug therapy.…”
Section: Discussionmentioning
confidence: 99%